Terreiro e cotidiano: contribuições para outras perspectivas de cuidado voltadas para pessoas negras - Santos, Anna Carolina (Universidade Federal de São Carlos, 2024)
This work proposes dialogues between the Everyday and the Terreiro, aiming to expand care perspectives for Black people through an immersion in Ilê Axé BaraKetu IyaSessu, located in the West Zone of Rio de Janeiro. The research, which takes a qualitative and autoethnographic approach, investigated the community's daily life and its system of cultural symbols from the perspective of Care. Interviews and the PhotoVoice technique were conducted with participants who had been frequenting the terreiro for over two years and volunteered to contribute to the research. Data analysis resulted in four thematic groups: Care and Non-Human Community Heritage, Care and Territoriality, Care and Traditional African Matrix Science of Terreiro, and Care and Sacred Commensality. The results strengthen discussions on Care in the field of Occupational Therapy and promote the inclusion of counter-hegemonic knowledge in the production of knowledge, contributing to a better understanding of care practices directed toward Black people based on Traditional African Matrix Knowledge of the Terreiro.
Terreiro and everyday life: contributions to other perspectives of care for black people
Keywords: Terapia ocupacional; Cuidado; Cotidiano; Comunidade tradicional; Occupational therapy; Care; Everyday life; Traditional community; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL